2003
DOI: 10.1002/ejic.200390151
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis and Characterisation of Two Novel Large‐Pore Framework Vanadium Silicates

Abstract: Two new large-pore sodium vanadium silicates, denoted AM-15 and AM-17 (Aveiro-Manchester, structures number 15 and 17) with framework composition Na 6 Si 14 V 4 O 39 and Na 4 CaSi 10 V 2 O 27 , respectively, are reported. Electron paramagnetic resonance (EPR), Fourier transform infrared (FTIR) and diffuse reflectance ultraviolet-visible (DR UV/Vis) spectroscopy reveal that as-prepared AM-15 contains both V IV and V V in a square pyramidal and tetrahedral coordination,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…EDS measurement gives the molar ratio of K:V=39.88:60.12=2:3, matching well with the chemical formula K 2 V 3 O 8 . FT-IR bands were observed at 991(m), 941(m), 926(w), 816(s), 739(s), 525(w), and 431(m) cm À1 and are assigned to the vibrational modes for VO 5 square pyramids and VO 4 tetrahedra [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…EDS measurement gives the molar ratio of K:V=39.88:60.12=2:3, matching well with the chemical formula K 2 V 3 O 8 . FT-IR bands were observed at 991(m), 941(m), 926(w), 816(s), 739(s), 525(w), and 431(m) cm À1 and are assigned to the vibrational modes for VO 5 square pyramids and VO 4 tetrahedra [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…3). Brandão et al (2002aBrandão et al ( , 2003 reported several new largepore vanadosilicates with unknown structure.…”
Section: Vanadosilicates and Niobosilicatesmentioning
confidence: 98%
“…V 3+ , V 4+ or V 5+ . Vanadium-bearing materials are in fact well known in heterogeneous catalysis due to their efficient activity for partial oxidation of hydrocarbons (Corma, 1997;Brandã o et al, 2003;Teixeira-Neto et al, 2009). Although several approaches were attempted to introduce vanadium into the frameworks of certain zeolites, only minor quantities up to 1.5 wt% (Dzwigaj et al, 2000) were successfully incorporated either at defect sites or loosely bonded to the zeolite surface (Rigutto & Bekkum, 1991;Centi et al, 1992;Sen et al, 1996;Dzwigaj, 2003;Tielens et al, 2008;Teixeira-Neto et al, 2009).…”
Section: Introductionmentioning
confidence: 99%